The Rocky horror picture show [videorecording (DVD)] - Adler, Lou; White, Michael; Sharman, Jim, 1945-; Curry, Tim; Sarandon, Susan, 1946-; Bostwick, Barry; O'Brien, Richard, 1942- (Twentienth Century Fox Home Entertainment, 2002)
A mixture of fantastical rock opera and horror movie spoof. A couple of ordinary kids have car trouble one dark and rainy night and knock on the door of a looming gothic mansion. They are stunned to learn that they have stumbled into an ongoing convention of kinky characters, hosted by Dr. Frank-N-Furter, a mad scientist from the planet Transsexual.